Formulation and Evaluation of Nanosponges of an Antileprosy Drug: Topical Application - Chandira, Rajappa Margret; Pethappachetty, Palanisamy; Chandiran, Gnanasekeran; Samy, Dominic Antony (Asian Journal of Biological and Life Sciences)
Recent advances in nanotechnology have concreted the way to develop nanogels with numerous potential applications in nanomedicine. When compared to other nanocarriers, nanosponges have a large drug loading capacity, making them ideal for resolving operational stability, solubility, and delayed-release, as well as designing drug delivery systems for routes other than oral administration. Nanosponges drug delivery systems have two key advantages: controlled release of loaded actives and improved solubility of poorly water-soluble medicines. The development of nanosponges as drug delivery systems is discussed in this article, with an emphasis on nanosponges based on the emulsion solvent diffusion approach. In this study, an attempt was made to improve drug solubility. It formulated nanosponges-based Dapsone topical gel using Ethylcellulose polymer in various concentrations and Polyvinyl alcohol as a surfactant, which was evaluated for pH, Viscosity, spreadability, percentage of drug release, and kinetics modelling release studies. Among all six formulations, the F5 batch was deemed to have the best entrapped (97%) nanosponges with the highest percentage of drug release (95.89%). The SEM analysis concluded that the formulation particles are porous. The particle size determination concluded that the particles are nano in size, which is recognized in the preparation as Nanosponges.
Keywords: Anti leprosy Drug; Dapsone topical gel; Emulsion solvent diffusion method; Emulsion solvent diffusion method.Nanosponges; Ethylcellulose polymer and Polyvinyl alcohol.; Nanomedicine; Nanosponges